Inactivation of SARS-CoV-2 by povidone-iodine products : implications for effective mouth rinsing and gargling - Hiroaki Kariwa; Hirofumi Sawa; Shintaro Kobayashi (The Japanese Journal of Veterinary Research, 2021)
[Abstract] Coronavirus disease 2019 (COVID-19) is caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). SARS-CoV-2 is transmitted mainly via droplets and contact. The implementation of infection control measures is important to reduce the number of COVID-19 cases. Thus, the ability of several povidone-iodine (PVP-I) products to inactivate SARS-CoV-2 was evaluated based on their in vitro inactivation efficacy. PVP-I solutions such as Isodine Gargle(R) (ethical and consumer products), Isodine Gargle C(R), and Isodine Nodo Fresh(R) for 30 or 60 s decreased the viral infectivity level from 2-4 × 106 TCID50/ml to below the detectable level (> 99.9% reduction). Our results indicate that the use of Isodine(R) mouthwash and gargle products is an effective infection control measure against SARS-CoV-2.